Fumonisins alter redox balance in Nile tilapia fingerlings - Lala, Bruno [UNESP]; Santos, Carolina [UNESP]; Roldi, Gabriel; Roça, Roberto [UNESP]; Sampaio, Guilherme [UNESP]; Garcia, André; Garrido, Bruno; Ricci, Gleia; Refundini, Gislaine; Braccini, Graciela; Porto, Carla; Gasparino, Eliane; et al. (Elsevier, 2021)
Fumonisins (FB) are secondary metabolites of Fusarium fungi, and their ingestion are associated with liver disease in different species of animals. This study tests the hypothesis that FB alter redox balance-related gene expression in Nile tilapia fingerlings. A total of 180 fish randomly distributed in four treatments were used: the control treatment (0.0), 20 (FB20), 40 (FB40) and 60 (FB60) mg/kg of FB, to evaluate Glutathione peroxidase (GPX) and heat shock protein (HSP70) mRNA expression in the liver. There was a significant effect of both treatment and exposure period for GPX, evidencing that the response is time-dependent. Similarly, there were exposure time (P <.0001) and diet (P <.0001) effects, as well as their interaction for HSP70 gene expression, but with an increase at 14 days and a reduction at 28 days, showing it to be inversely proportional to GPX. The FB exposure in Nile tilapia fingerlings affects the expression of the genes involved in GPX and HSP70 redox equilibrium, with HSP70 expression initially increased and positive feedback response to GPX, which, in turn, promotes negative feedback response to HSP70 with longer periods of exposure.
Keywords: Fusarium moniliforme; Mycotoxin; Oreochromis niloticus; Oxidative stress